Multimetallic Porphyrins/Polyoxotungstate Modified Electrodes by Layer-By-Layer Method: Electrochemical, Spectroscopic and Morphological Characterization - Aguirre-Quintana, M; Aguirre-Quintana, M (2012)
This work describes the formation of modified electrodes layer-by-layer assembly of a ?-{meso-5,10,15,20-tetra(pyridyl)porphyrin} tetrakis{bis(bipyridine)chloride ruthenium(II)} coordinated with Zn(II) and Mn(III) in its central cavity and an anionic polyoxotungstate [SiW 12O 40] 4-. The bilayer formation was monitored using electrochemical and UV-vis techniques, following the oxidation process of the Ru III/II couple and the absorbance of the Soret band of porphyrin complexes respectively. It was possible to form 10 stable bilayers onto ITO surface. SEM studies were carried out finding that the morphology of the film depends on the metal center in the porphyrin. The thickness of these films was estimated as 0.603 ?m for [Zn(II)TRP] 4+/[SiW 12O 40] 4- and 2.18 ?m for [Mn(III)TRP] 5+/ [SiW 12O 40] 4- modified electrodes respectively. Raman spectroscopy showed that new bands appeared for [Mn(III)TRP] 5+/[SiW 12O 40] 4- assembly confirming stronger interactions than only electrostatic forces. Kinetics parameters such as charge transfer coefficient, ?, and heterogeneous electron transfer rate constant, k s were obtained for both electrodes. Using electrochemical and UV-vis data it was possible to estimate the energy levels involved in the charge transfer process through the films formed. Sensor properties of [Zn(II)TRP] 4+/[SiW 12O 40] 4- modified electrode toward chlorite oxidation was tested. The results show electrocatalytic activity, amperometric determination demonstrate a detection limit of 13.8 ?M. © 2012 Elsevier Ltd.